Comparison of Acute Physiology and Chronic Health Evaluation (APACHE) II Scoring System and Inflammation-Nutrition-Consciousness-Neurologic Function-Systemic Condition (INCNS) as Predictors of Mortality in Neurosurgical Patients in the Intensive Care Unit - Widiastuti, Monika; Bisri, Dewi Yulianti; Rachman, Iwan Abdul (Migration Letters, 2023)
Introduction: We aimed to determine the prognostic significance of INCNS compared to APACHE II in predicting mortality for neurocritically ill patients. Methods: The study involved neurosurgical ICU patients, and data collection followed a prospective cross-sectional approach. The collected data underwent editing, coding, processing, and cleaning before statistical analysis using SPSS. The primary outcome of current study is mortality. Mortality was defined as the condition of patients who passed away while still under ICU care. Results: A total of 77 patients who met the inclusion criteria for this study. The average age of the patients in this study was 50.87 years. Of this total, 37 (48.1%) were male and 40 (51.9%) were female. The APACHE II score yielded a cut-off point of 22.5, with a sensitivity of 66.7%, specificity of 64.7%, positive predictive value of 80%, and negative predictive value of 93.6%. The INCNS score resulted in a cut-off point of 16, with a sensitivity of 77.8%, specificity of 97.1%, positive predictive value of 97.1%, and negative predictive value of 77.8%. Both assessment systems showed goodness-of-fit statistical tests with p > 0.05, with INCNS (Hosmer-Lemeshow statistic = 45.207, p < 0.001) demonstrating better fit compared to APACHE II (Hosmer-Lemeshow statistic = 3.753, p = 0.053). Conclusion: The research results suggest that the INCNS score is a valuable tool for predicting patient outcomes and optimizing patient management strategies in neurosurgical ICU settings. Further validation studies are warranted to establish the reliability and widespread adoption of the INCNS score in neurocritical care practice.